Geo-Exploration Outdoors: Utilizing Green Open Spaces for Learning Geography Concepts - Angel Hidayat; Dedi Hermon (Postgraduate, University of Mataram, 2025)
This study aims to analyze the effectiveness of the use of Green Open Space (RTH) as a contextual learning medium to improve students’ understanding of geographic concepts at MAN 3 Kampar. The research employed a quasi-experimental design with a pretest–posttest one-group approach involving 32 tenth-grade students selected through purposive sampling. Learning activities integrated digital tools such as Google Earth, Google Maps, and Augmented Reality (AR) during three outdoor sessions conducted in August 2025. Data were collected using multiple-choice cognitive tests, observation sheets for the skills and affective domains, and student reflection questionnaires. Quantitative data were analyzed using descriptive statistics and N-Gain tests, while qualitative data from reflections supported the interpretation of students’ learning engagement. The results showed a mean cognitive score improvement from 71.12 to 88.27 (N-Gain = 0.59, moderate) and an increase in the affective-skill score from 65.84 to 78.23. These findings indicate that RTH-based digital exploration effectively enhances geospatial literacy, critical thinking, and environmental awareness. Despite challenges such as limited equipment and weather variability, strategic preparation ensured smooth implementation. The study concludes that integrating outdoor and digital learning supports the Merdeka Curriculum’s goals of contextual and meaningful education in madrasah settings.